Conserved Residues Control Activation of Mammalian G Protein-Coupled Odorant Receptors - de March, Claire A. (J Am Chem Soc, 2015)
Odorant Receptor (OR) genes and proteins represent more than 2% of our genome and 4% of our proteome 25 and constitute the largest sub-group of G Protein-Coupled Receptors (GPCRs). The mechanism underlying OR activation remains poorly understood, as they do not share some of the highly conserved motifs critical for activation of non-olfactory GPCRs. By combining site-directed mutagenesis, heterologous expression, and molecular dynamics simulations that capture the conformational change of constitutively active mutants, we tentatively identified crucial residues for the function of these receptors using the mouse MOR256-3 (Olfr124) as a model. The toggle-switch for sensing agonists in-volves a highly conserved tyrosine residue in helix VI. The ionic-lock is located between the `DRY' motif in helix III and a positively charged `R/K' residue in helix VI. This study provides an unprecedented model that captures the main mechanisms of odorant receptor activation.